The Influence of the Problem Solving Model on Science Subjects Ecosystem Material on the Learning Outcomes of Grade V Students of SDN 1 Kawo Year 2022/2023 - Gilang Fastian Hajiji; Muhammad Makki; Muhammad Tahir (Journal of Business Social and Technology, 2024)
The purpose of this study was to determine the effect of the application of the Problem Solving method on the learning outcomes of Natural Sciences in class V SDN 1 Kawo. The type of research used by researchers in this study is the type of Quasi Experimental Design. The research method used is experimental research. In this study, there were two class groups, namely the experimental class and the control class. The experimental class is a class that is given treatment in the form of Problem Solving methods while the control class is a class that uses conventional methods. Based on the results of data analysis and discussion entitled the influence of problem solving models on science lessons, ecosystem material on the learning outcomes of grade V students of SDN 1 Kawo, there are t test results and it is known that the average pre-test is 18.21 after a post-test of 21.00 so that the increase is 2.79. Furthermore, based on the t test, a calculated value of 15.694 was obtained. The t value of the table with df 32 at a significant level of 5% is 2.037. Therefore t count> ttableOr ( 15.694 > 2.037) and the significance value is smaller than 0.05 (0.00 < 0.05) so that it can be stated that there is a significant increase in the learning outcomes score of experimental group students or those given learning with the Problem Solving model.